FP_Tree ASSOCIATION RULE MINING ECOMMERCE PRODUCT ADVERTISING EFFORTS TO IMPROVE PRODUCT BRAND SALES STRATEGY TO SUPPORT ECOMMERCE BUSINESS IN INDONESIA - Wanra Tarigan; Thamrin Thamrin; Lismardiana Sembiring; Iswanto Sembiring; Harlen Silalahi; Tulus Pramita Sihaloho (International Journal of Social Science, 2021)
The increasing growth of e-commerce in Indonesia makes research on online marketplaces an interesting topic to research. Several factors, such as buyer reviews and ratings, the ease of buying and selling transactions, shipping costs (postage), the reputation of the e-commerce platform, and also the reputation of the store itself (seller) are considered by buyers in choosing an online store. The more platforms there are, the more intense the competition between online marketplaces will be. With that, many start-up companies B2B (Business to Business), or B2C (Business to Customer), C2B (Customer to Business), C2C (Customer to Customer), which stated that many of their products were sold with fantastic sales figures. But there are also some products that need to be developed for sales due to the lack of product advertisements being broadcast and launched on a large scale because these products are considered good for future prospects and profitable for the company.